A Preliminary Study Looking at the Use of Mindful Compassion and Cannabis Suppositories for Anodyspareunia among Men Who Have Sex with Men (MSM) - Samantha Banbury; Chris Chandler; Simon Erridge; Javier del Rio Olvera; John Turner; Joanne Lusher (MDPI AG, 2024)
Research on the use of cannabis rectal suppositories for analgesia is limited. Few trials have evaluated the combined use of mindfulness and cannabis suppositories for anodyspareunia in men who have sex with men (MSM). This preliminary study, including a randomised control trial (RCT) and content analysis, assessed the effectiveness of an online mindful-compassion and cannabis suppository intervention among 52 British MSM (aged 18-50) who predominantly identified as bottoms (recipients of anal sex). Participants were randomly allocated to one of four groups based on whether they were using cannabis suppositories: adjunct cannabis suppository and mindful-compassion (CSMF), cannabis suppository only (CS), mindful compassion only (MF) and care as usual/control (CAU). Assessments measuring mindful compassion, sexual functioning, sexual self-efficacy, well-being, and anodyspareunia levels were completed at weeks 0, 4, and 12. Anodyspareunia levels were lower in the CSMF group compared to the other groups (CS/MF/CAU), p = 0.031. Feedback revealed that participants felt mindful compassion potentiated the effects of cannabis suppositories during sexual intimacy, reducing pain and enhancing sexual self-efficacy, sexual functioning, and well-being. This preliminary study warrants larger-scale investigation to establish the role of cannabis suppositories and mindful compassion in reducing anodyspareunia.